Una mirada crítica al discurso de los textos escolares sobre el stronismo - Sandra D’Alessandro de Valdez (Centre de Recherches sur les Mondes Américains, 2014)
Paraguayan History textbooks portraying the “stronista” regime in this country, published between 1970 and 2008, which are used in middle schools, are submitted to a critical discourse analysis. Thus, a macro and micro semantic analysis are carried out according to the analysis categories from T. van Dijk, and making reference to what’s hidden in their discourse.Representations of the stronismo are adapted to the democratic reality of the country, including aspects that emphasize its negative perception. However, there are still a few opinions strongly rooted in the idea of peace and prosperity during this regime, which become decisive in the formation of the young students’ mentality. Descriptions of the repressions and its tools during the regime as well as its violation of human rights are omitted. As a result, the new generation risks not being able to recognize traces of this period of history.